Incorporation of a redox-active bis(guanidine) in low-dimensional tin and lead Iodide structures - Herrmann, Hendrik Hans; Walter, Petra; Kaifer, Elisabeth; Himmel, Hans-Jörg (European journal of inorganic chemistry, 2017)
Redox-active, protonated guanidines are incorporated in tin and lead iodide structures to protect the metal atoms from being oxidized and to thereby increase the stability of these materials. They could serve as preferred place of attack for incoming dioxygen, reducing it to redox-inactive water, while being themselves oxidized to a stable dication without significant structural changes. This work focuses on the synthesis and bulk characterization of two first examples for tin and lead iodide materials with redox-active guanidines.